Evolutionary dynamics of spatial games - Ekesryd, Olle (My University, 2020)
Game theory is a subject that can be applied to many fields of study, for instance biology and economics. In this report, we look at two known games in game theory, Prisoner’s dilemma and Hawk dove. In contrast to previous research on these two games, every agent is located in two-dimensional space on the unit square. This spatial case on game theory changes the dynamics of the games. For example, we found that cooperating is a superior strategy in Prisoner’s dilemma, for some combinations of parameters. For reference, in the normal Prisoner’s dilemma, the strategy defect dominates the strategy to cooperate. It is also found that the initial state of the simulations has a big impact on the results obtained. The simulations made are computationally demanding. An attempt was therefore made to make approximations that could replace the spatial model. The result from the approximations shows that it is not good enough to replace the spatial model. However, steps has been made that can help future researchers to make an approximation that works well.
Keywords: spatial game theory, evolutionary dynamics, Prisoner’s dilemma, Hawk dove